Bos Taurus cattle sperm integrity effect by cryopreserved semen manpulation (2016)
This study evaluated the semen thawing and application effect in 33 bovine cattle farms in the Colombian Magdalena Medio region and studied in vitro, the injury effect found on the integrity of sperm membranes. The information was collected in farms by a specific paper form, The in vitro study was carried out in the Reproductive Animal Biotechnology laboratory at the Instituto Universitario de la Paz (Barrancabermeja, Santander, Colombia). The study consisted of exposing commercial 0.5 ml straws of bull Holstein and Brown Swiss to the conventional technique, and three modifications thereof (injuries) by a randomized design. None of the farms evaluated applied correctly the practice of artificial insemination. Evident errors were: Time excess for extraction of the straw, thawing in the axillary region and incorrect combination of time and temperature. The results showed significant difference (P <0.05) by the race effect for the integrity and strength of the plasma membrane, also for the integrity ofthe membranes by treatment effect, when the straw was thawed at body temperature in the axillary region and for the integrity of the acrosomal membrane when extraction straw was performed incorrectly. Holstein semen evidences a slight tendency to be more resistant than the Brown Swiss breed.